Pelatihan Penerapan Learning Management System (LMS) bagi Guru Dalam Tantangan Era Blended Learning - Amelia, Tan; Sunarto, M. J. Dewiyani; Hariadi, Bambang; Sagirani, Tri; Lemantara, Julianto (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase teacher understanding and optimize the implementation of the Learning Management System (LMS) in the blended learning era. The method for implementing this service uses training in the form of webinars with 119 teachers spread across 40 cities in Indonesia. The evaluation instrument for this activity uses a questionnaire, which is analyzed descriptively. The results of this service activity show an increase in teachers' understanding of implementing LMS. The results are evidenced by teachers' increasing knowledge about making LMS an online classroom, especially in providing teaching materials and setting student assignments and exams.